Autoantibodies and the Risk of Cardiovascular Events - Liang, Kimberly P. (2009)
OBJECTIVE: Inflammation and autoimmunity are associated with increased cardiovascular (CV) risk in rheumatoid arthritis patients. This association may also be present in those without rheumatic diseases. The purpose of this study was to determine whether rheumatoid factor (RF), antinuclear antibody (ANA), and cyclic citrullinated peptide antibody (CCP) positivity are associated with increased risk of CV events and overall mortality in both those with and without rheumatic diseases. METHODS: We performed a population-based cohort study of all subjects who had a RF and/or ANA test performed between 1/1/1990 and 1/1/2000, and/or CCP test performed between 9/1/2003 and 1/1/2005, with follow-up until 4/1/2007. Outcomes were ascertained using diagnostic indices from complete medical records, including: CV events [myocardial infarction (MI), heart failure (HF), and peripheral vascular disease (PVD)], and mortality. Cox models were used to analyze the data. RESULTS: There were 6783 subjects with RF, 7852 with ANA, and 299 with CCP testing. Of these, 10.4%, 23.9% and 14.7% were positive for RF, ANA and CCP, respectively. Adjusting for age, sex, calendar year, comorbidity and rheumatic disease, RF and ANA positivity were significant predictors of CV events (HR 1.24 & 1.26) and death (HR 1.43 & 1.18). Adjusting for age, CCP positivity was associated with CV events but this association was not statistically significant (HR 3.1; 95% CI 0.8, 12.3). CONCLUSIONS: RF and ANA positivity are significant predictors of CV events and mortality in both those with and without rheumatic diseases. These results support the role of immune dysregulation in the etiology of CV disease.